2005
DOI: 10.1080/15216540500090611
|View full text |Cite
|
Sign up to set email alerts
|

Stress Responses in Mycobacteria

Abstract: SummaryMycobacterium tuberculosis is a successful pathogen that overcomes numerous challenges presented by the immune system of the host. This bacterium usually establishes a chronic infection in the host where it may silently persist inside a granuloma until, a failure in host defenses, leads to manifestation of the disease. None of the conventional anti-tuberculosis drugs are able to target these persisting bacilli. Development of drugs against such persisting bacilli is a constant challenge since the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 60 publications
1
41
0
1
Order By: Relevance
“…Attack at a sugar leads to sugar fragmentation as well as loss of base resulting in strand break. Radicals can also damage the bases of the DNA such as ring-saturated thymines, hydroxyl methyl uracil, thymine fragments and adenine ring opened products [15,16]. The results in this study showed that upon increasing oxidative and pH values more clump formation was detected.…”
Section: Resistence Tosupporting
confidence: 59%
“…Attack at a sugar leads to sugar fragmentation as well as loss of base resulting in strand break. Radicals can also damage the bases of the DNA such as ring-saturated thymines, hydroxyl methyl uracil, thymine fragments and adenine ring opened products [15,16]. The results in this study showed that upon increasing oxidative and pH values more clump formation was detected.…”
Section: Resistence Tosupporting
confidence: 59%
“…Although free radical production has been shown to have minimal effects on the survival of M. tuberculosis, there are little data on the effects of superoxide and nitric oxide production on M. abscessus viability (8,25). We found that THP-1 cells produced little superoxide in response to the phagocytosed M abscessus.…”
Section: Discussionmentioning
confidence: 71%
“…It has been shown that another mycobacterium species, M. tuberculosis, can withstand oxidative environments inside macrophages by up-regulating redox-sensing proteins (8). M. tuberculosis is somewhat susceptible to nitric oxide production; when nitric oxide production is blocked, certain strains of M. tuberculosis displayed enhanced intracellular growth (25).…”
Section: Mnte-2-pyp Does Not Reduce Intracellular Growth Of M Abscesmentioning
confidence: 99%
See 1 more Smart Citation
“…This consensus for SigF-dependent promoters in M. smegmatis was identified as GTTT-N (15)(16)(17) -GGGTA ( Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%